Human T-lymphotropic virus 1/2 infection among prisoners of a major penitentiary complex of Goiás State, Central-West Brazil - Okita, Michele Tiemi; de Matos, Marcos André; Freitas, Nara Rúbia de; Silva, Ágabo Macedo da Costa e; Marques, Juliana Menara de Souza; Marinho, Thaís Augusto; Matos, Márcia Alves Dias de; Martins, Regina Maria Bringel (Frontiers in Public Health, 2024)
Studies on human T-lymphotropic virus 1/2 (HTLV-1/2) infection are scarce in incarcerated population. Therefore, this study estimated the prevalence of HTLV-1/2 infection among prisoners of the major penitentiary complex of Goiás State, Central-West Brazil, comparing it with available data from other Brazilian regions.A cross-sectional study was conducted with 910 prisoners of the major penitentiary complex in the State of Goiás, Central-West Brazil. All participants were interviewed, and their serum samples were tested for anti-HTLV-1/2 using an enzyme-linked immunosorbent assay (ELISA; Murex HTLV-I+II, DiaSorin, Dartford, UK). Seropositive samples were submitted for confirmation by a line immunoassay (INNO-